Optimized pediatric emergency nursing and Its effects on successful resuscitation and adverse reactions in children - Zhang, Xia; Chen, Xiao (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate impacts of optimized pediatric emergency care on successful resuscitation and adverse events of children in the emergency department.MethodsPediatric patients who visited our hospital's emergency room between January 2022 and December 2023 were chosen as the study participants. These patients were randomly divided into the study group (using optimized emergency care model) and the control group (using conventional emergency care model). The two groups were compared for the rate of successful resuscitation, stabilization time of vital signs, average length of hospital stay, incidence of adverse reactions, parental satisfaction with nursing care, scores of Self-Assessment Scale of Anxiety (SAS) and Self-Assessment Scale of Depression (SDS) before and after nursing care, and assessment of life quality.ResultsA total of 140 children were included in this study. Seventy patients each were assigned to study and control groups. After the intervention, the study group's successful resuscitation rate was considerably greater than the control's (P < 0.05). For the study group, the optimized care intervention significantly reduced the stabilization time of vital signs and the typical duration of hospitalization compared with the control group (P < 0.001). Compared to the control group, the study group had a lower incidence of adverse reactions (P < 0.05), a higher level of parental satisfaction (P < 0.05), significant reduction of the SAS and SDS scores (P < 0.001), and significant elevation of the quality of life scores (P < 0.001).ConclusionThe study demonstrates that the optimized pediatric emergency care intervention is an effective approach for improving the successful resuscitation of children in emergency medicine, and mitigate the incidence of adverse reactions. Concurrently, the optimized nursing intervention was found beneficial for anxiety and depression levels, with a notable improvement in their quality of life as well as parental satisfaction. Optimized nursing interventions therefore are valuable and are recommended for wider pediatric emergency care practice.